Optimizing first line 7‐day standard triple therapy for Helicobacter pylori eradication: Prolonging treatment or adding bismuth: which is better? - Leow, Alex Hwong Ruey; Azmi, Ahmad Najib; Loke, Mun Fai; Vadivelu, Jamuna; Graham, David Yates; Goh, Khean Lee (Wiley, 2018)
Objective: The 7-day standard triple therapy (STT) gives unacceptablly low eradication rates of Helicobacter pylori (H. pylori). We aimed to examine whether extending STT from 7 days to 14 days or adding a bismuth compound to a 7-day STT would result in better eradication rates. Methods: H. pylori-positive patients were assigned to Group A (7-day STT; rabeprazole 20 mg twice daily, amoxicillin 1 g twice daily, and clarithromycin 500 mg twice daily, for 7 days), Group B (7-day STT with bismuth; rabeprazole 20 mg twice daily, amoxicillin 1 g twice daily, clarithromycin 500 mg twice daily and bismuth subcitrate 240 mg twice daily, for 7 days) and Group C (14-day STT; rabeprazole 20 mg twice daily, amoxicillin 1 g twice daily, and clarithromycin 500 mg twice daily for 14 days). Eradication was tested using 13 C-UBT at least 4 weeks after the completion of therapy. Results: A total of 364 patients were recruited. In the intention-to-treat analysis, eradication rates were 79.3% (96/121; 95% confidence interval [CI] 71.3–85.6%) for 7-day STT, 81.7% (98/120; 95% CI 73.8–87.6%) for 7-day STT with bismuth, and 88.6% (109/123; 95% CI 81.8–93.1%) for 14-day STT, respectively. Statistical significance was achieved between the 7-day and the 14-day STT treatment (P = 0.048). Conclusions: Adding bismuth to the 7-day STT did not result in an increase in the eradication rate. Extending the STT to 14 days, however, achieved a significantly higher eradication rate. Nevertheless, this did not achieve the targeted 90% eradication rate on intention-to-treat analysis.